THE APPROACH OF RELIGIOUS PLURALISM IN PUBLIC POLICY: AN ANALYSIS OF PRESIDENTIAL REGULATION NUMBER 58 OF 2023 - Wajdi, Muh Barid Nizarudin; Fathurrohman, Amang; Pamungkas, Muhamad Imam (Universitas Nasional, 2024)
Indonesia’s diverse religious landscape offers both opportunities and challenges in fostering societal harmony. Presidential Regulation No. 58 of 2023 on Strengthening Religious Moderation integrates principles of relational pluralism, managed pluralism, and religious institutional pluralism to promote interfaith dialogue, inclusivity, and public safety while respecting the autonomy of religious communities. This qualitative study, based on document analysis, interviews, and observations, reveals that the regulation facilitates collaboration between state and religious groups, increases participation in interfaith initiatives, and reduces prejudice, particularly among younger demographics. Despite these successes, challenges such as cultural resistance, uneven implementation, and limited understanding of pluralism persist. The findings contribute to the discourse on pluralism by connecting theoretical frameworks with practical applications in Indonesia’s unique socio-religious context and offer recommendations for enhancing policy effectiveness through education, capacity building, and strategic implementation.